Pengaruh Dewan Komisaris, Komite Direksi dan Enterprise Risk Management Disclosure terhadap Nilai Perusahaan - Lestari, Diani; Santoso, Budi; Hermanto, Hermanto (E-Jurnal Akuntansi; Vol 30 No 4 (2020)DO - 10.24843/EJA.2020.v30.i04.p12, 2020)
This research analyzes whether there is an effect of board commissionaire, risk management committee as one of board od director’s committee and enterprise risk management disclosure towards firm value. The sample of this research is 31 financial companies listed in Indonesia Stock Exchange for the period 2016-2018. Regression analysis of panel data with the random-effect model was applied to analyze the data. The results show the risk management committee has a negative and significant effect on the firm value, whereas the effect board of commissionaire and enterprise risk management disclosure towards firm value does not significant. The result of this research is can be used as a consideration for the management and the regulator to encourage companies to established risk management committees for effective implementation risk management. Keywords: Board Of Commissionaire; Risk Management Committee; Enterprise Risk Management Disclosure; Firm Value.